2023
DOI: 10.3389/fpls.2023.1144113
|View full text |Cite
|
Sign up to set email alerts
|

The dissection of tomato flavor: biochemistry, genetics, and omics

Abstract: Flavor and quality are the major drivers of fruit consumption in the US. However, the poor flavor of modern commercial tomato varieties is a major cause of consumer dissatisfaction. Studies in flavor research have informed the role of volatile organic compounds in improving overall liking and sweetness of tomatoes. These studies have utilized and applied the tools of molecular biology, genetics, biochemistry, omics, machine learning, and gene editing to elucidate the compounds and biochemical pathways essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 133 publications
(273 reference statements)
0
9
0
Order By: Relevance
“…It has been found that phenolic acids and flavonoids are essential compounds for sustaining great quality in postharvest fruit [ 27 ]. Also, they are a crucial source for tomato flavor construction [ 42 ]. In Inonotus obliquus , both higher cellular NO content and GSNOR inhibition could raise polyphenol production, illustrating the role of NO and GSNOR in phenol biosynthesis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that phenolic acids and flavonoids are essential compounds for sustaining great quality in postharvest fruit [ 27 ]. Also, they are a crucial source for tomato flavor construction [ 42 ]. In Inonotus obliquus , both higher cellular NO content and GSNOR inhibition could raise polyphenol production, illustrating the role of NO and GSNOR in phenol biosynthesis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in LSL, the accumulation of both leucine as well as the nitrogen- and sulfur-containing compounds 2-isobuthylthiazole (wasabi, leafy odor) and 3-methylbutanenitrile (pungent) were induced, suggesting that the pathway is stimulated towards the production of these compounds. These leucine-derived compounds are very abundant in tomato fruit, being synthesized by the conjugation of 3-methylbutanal with cysteine ( Liscombe et al., 2022 ; Kaur et al., 2023 ). However, the underlying key gene, tetrahydrothiazolidine N-hydroxylase ( Wang et al., 2023 ), was not differentially expressed between genotypes, suggesting that other factors may also be important.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying key gene, tetrahydrothiazolidine N-hydroxylase ( Wang et al., 2023 ), was not differentially expressed between genotypes, suggesting that other factors may also be important. All the above-mentioned BCAA-derived compounds, found in either of the two genotypes, have been associated with liking by consumers ( Kaur et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following key volatiles affect the nutritional quality of tomato fruits and have been associated with particular aromas favored by consumers: 2-phenylacetaldehyde (floral), 3-methylbutanol (malt), 6-methyl-5-hepten-2-one (fruity and floral), and hexanal (grassy). A number of other volatiles are known to underlie aromatic, sour, and sweet flavors in tomato fruits [ 6 , 7 ]. Organic volatiles account for 62% of the sweet and 22% of the sour flavors of tomato fruits [ 8 ].…”
Section: Introductionmentioning
confidence: 99%